Pembuatan Aplikasi Pengarsipan Elektronik Berbasis Macro VBA Excel Pada Bank Woori Saudara Kantor Cabang Diponegoro - Purnama, Muhamad Reza Tresna; Gaffar, Mohammad Rizal; Pramono, Tangguh Dwi; Firmansyah, Yayan (Ebiz Prima Nusa, 2022)
Bank Woori Saudara KC Diponegoro is one of the branch offices of PT. Bank Woori Saudara Indonesia 1906, Tbk. which is engaged in commercial banking. In carrying out its banking activities, Bank Woori Saudara always involves important files that will be used for dealing with a customer. One example of such a file is the CIF Application Document which contains a number of important customer-related information. The collection of archives is stored and managed by the Front Office Department at Bank Woori Saudara. In managing the archives of the frontliner staff, a manual storage system is used, where the documents are stored based on the order and CIF number located in the available filling cabinet. The lack of archival management and an adequate record-keeping system causes frontliner staff to often find it difficult to search for the required documents. Therefore, in order to meet fast-paced technological developments and an adequate archive management system, an electronic filing application was created. This application is expected to help frontliner staff in carrying out operational activities, especially for information needs. In doing the design and manufacture, the application uses the Macro VBA Excel system so that it has an easy-to-reach appearance and work.